Measuring Malaysian public perception with secret-eye / Siti Zaleha Zainal Abidin, Nasiroh Omar and M. Hamiz M. Radzi - Zainal Abidin, Siti Zaleha; Omar, Nasiroh; M. Radzi, M. Hamiz (CMIWS and UiTM Press, 2011)
People’s perception and emotion are usually measured through conducting a survey research. With the rigid multiple choice or lickert scale selection of answers, participants have to respond within a given time frame to give their feedback on a certain specified issue. In this paper, we present our research through collecting data regarding people’s perception and emotion through an online forum. We quantify the data and perform data classification based on issues and emotion. Data collection are carried out by using an implemented software tool called Secret-Eye which is capable of extracting all significant words in the forum unobtrusively at real time real life basis. The classified data are ranked according to their frequency of existence. The discussion on the tsunami disaster in Japan that happened in March 2011, is selected for this study. It is beneficial to have the results on the perception analysis as public’s feelings and facts on the discussion are expressed naturally. Thus, the results indicate that it is feasible to extract people’s true means of perception through social media.